2013
DOI: 10.9775/kvfd.2012.8315
|View full text |Cite
|
Sign up to set email alerts
|

Erken ve Geç Laktasyon Periyodunun Keçilerde Plazma Oksidan/Antioksidan Dengesi Üzerindeki Etkileri

Abstract: SummaryThe purpose of the study was to investigate effects on oxidant and antioxidant balance of early and late lactation period in goats. Blood samples used in study were obtained from Halep goats in early and late lactation period. Oxidative stress index (OSI) and lipid hydroperoxide (LOOH) and total oxidative status (TOS) and total antioxidant status (TAS) were analyzed to determined of oxidant and antioxidant balance. Plasma TOS, OSI and LOOH levels in early lactation period were significantly higher (P<0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…Both reactive oxygen species and antioxidants have major physiological roles in all reproductive processes. This is similar to Karapehlivan et al (2012) that antioxidant potential reduced and oxidative stress increased in early lactation goats. And the depletion of critical antioxidant defense components in tissues may predispose to metabolic changes which originated from oxidative stress.…”
Section: Discussionsupporting
confidence: 85%
“…Both reactive oxygen species and antioxidants have major physiological roles in all reproductive processes. This is similar to Karapehlivan et al (2012) that antioxidant potential reduced and oxidative stress increased in early lactation goats. And the depletion of critical antioxidant defense components in tissues may predispose to metabolic changes which originated from oxidative stress.…”
Section: Discussionsupporting
confidence: 85%
“…Studies in Red Syrian goats report a significant decrease in glutathione peroxidase (GPX) activity and albumin concentration during the peripartum, suggesting that animals experienced moderate oxidative stress during this period [9]. Changes in total oxidative and antioxidant status were observed in local goats from early lactation to late lactation period and it was supposed to be associated to a different lipomobilization occurring in adipose tissue along the lactation period [10]. An influence of parity on the occurrence of peripartum redox imbalance was also observed when the metabolic and antioxidative status of Saanen goats of different parity were compared [11].…”
Section: Introductionmentioning
confidence: 99%
“…Aydın and Köse (2015) reported that MDA serum concentrations in Saanen goats decreased significantly during pregnancy and lactation compared to pre-pregnancy values and reached the lowest value in the 3 rd month of pregnancy, while AO levels reached the highest value in the same periods. Karapehlivan et al (2013) found that TAS levels were lower in early lactation goats compared to late lactation goats, while TOS and OSI levels were significantly higher. The same researchers reported that there were significant differences in MDA levels between early and late lactation periods of goats (Karapehlivan et al 2013).…”
Section: Resultsmentioning
confidence: 84%
“…Karapehlivan et al (2013) found that TAS levels were lower in early lactation goats compared to late lactation goats, while TOS and OSI levels were significantly higher. The same researchers reported that there were significant differences in MDA levels between early and late lactation periods of goats (Karapehlivan et al 2013).…”
Section: Resultsmentioning
confidence: 84%